Effect of adding different types of soluble fibre to high-protein yoghurts on water holding capacity, particle size distribution, apparent viscosity, and microstructure. (June 2023) - Gomes, Elisângela Ramieres; Barroso dos Anjos Pinto, Caroline; Stephani, Rodrigo; Fernandes de Carvalho, Antônio; Perrone, Ítalo Tuler
Abstract: The effect of different types of fibre (70% soluble corn fibre, 85% soluble corn fibre, and polydextrose) and fibre concentrations (2.5%, 5%, and 10%) on high-protein non-fat no-added-sugar yoghurt was evaluated. During fermentation, yoghurts with 10% fibre concentration had a faster pH reduction. The types of fibre tested did not affect the water holding capacity (WHC) of the yoghurts relative to that of the control. On day 0, independently of the fibre type, higher fibre concentrations resulted in a smaller particle size distribution ( d 90 ). After storage for 45 days, there was no difference in viscosity between the yoghurts treated with added fibre and the control. The microstructure of yoghurt with 10% polydextrose showed larger pores, possibly due to the increased concentration of fibre. These results are promising for industries wishing to produce yoghurt with differentiated characteristics, such as high protein content and added fibre.